Understanding young Buddhists : living out ethical journeys - Page, Sarah-Jane. (International Studies in Religion and Society, 2017)
There is currently an acute lack of scholarly engagement with Buddhism and youth. Based on ground-breaking empirical research, Understanding Young Buddhists: Living out Ethical Journeys explores the stories of young Buddhists, through a rich analysis of their lived experiences. Page and Yip explore their journeying into Buddhism, their Buddhist belief and practice, their management of sexuality, and their social positioning in relation to family and kin, friendship networks, youth culture, and occupational aspirations. Using lived religion as a theoretical lens, and bringing into dialogue research on Buddhism and youth, Understanding Young Buddhists convincingly demonstrates the resourcefulness and creativity of young Buddhists in developing ethics for life, as they negotiate the diverse challenges and opportunities in their journeys of life.